AHNS Series: Do you know your guidelines? Optimizing outcomes in reoperative parathyroid surgery: Definitive multidisciplinary joint consensus guidelines of the American Head and Neck Society and the British Association of Endocrine and Thyroid Surgeons. Issue 8 (2nd August 2018) - Stack, Brendan C.; Tolley, Neil S.; Bartel, Twyla B.; Bilezikian, John P.; Bodenner, Donald; Camacho, Pauline; Cox, Jeremy P. D. T.; Dralle, Henning; Jackson, James E.; Morris, John C.; Orloff, Lisa Ann; Palazzo, Fausto; et al.
Abstract: Background: Revision parathyroid is challenging due to possible diagnostic uncertainty as well as the technical challenges it can present. Methods: A multidisciplinary panel of distinguished experts from the American Head and Neck Society (AHNS) Endocrine Section, the British Association of Endocrine and Thyroid Surgeons (BAETS), and other invited experts have reviewed this topic with the purpose of making recommendations based on current best evidence. The literature was also reviewed on May 12, 2017. PubMed (1946‐2017), Cochrane SR (2005‐2017), CT databases (1997‐2017), and Web of Science (1945‐2017) were searched with the following strategy: revision and reoperative parathyroidectomy to ensure completeness. Results: Guideline recommendations were made in 3 domains: preoperative evaluation, surgical management, and alternatives to surgery. Eleven guideline recommendations are proposed. Conclusion: Reoperative parathyroid surgery is best avoided if possible. Our literature search and subsequent recommendations found that these cases are best managed by experienced surgeons using precision preoperative localization, intraoperative parathyroid hormone (PTH), and the team approach.